Periodontitis as a risk factor for preterm labour and low birth weight among pregnant women attending a tertiary care teaching hospital - Chokkaiyan, Saranya; Arumugam, Sendhil Coumary; Kumar, Saravana; John, Lopa B; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm birth is the single most important factor affecting perinatal outcome in terms of both morbidity and mortality. Chronic infections in mother are being implicated as a cause of preterm labour. The objective of this study was to find out a causal association between periodontitis and preterm labour or low birth weight. It was a Case- Control Study. This study was conducted in Mahatma Gandhi Medical College and Research Institute, Puducherry between February 2013 and June 2014. Methods: A total of 200 women were included in the study with 100 women in each group (cases and controls). Cases included women who had spontaneous preterm labour or threatened PTL (gestational age 28- 36 weeks) or women who had delivered a baby with the birth weight being less than 2.5 kg. Controls were patients who had a normal labour with the gestational age of more than 37 weeks with birth weight of the baby more than 2.5 kg. Periodontal examination was done for both cases and controls. Periodontal factors like Plaque Index (PI), bleeding Index (SBI), Probing pocket depth (PD) and Clinical attachment level (CAL) were examined for both groups. Student t test, Chi-square and Fisher Exact has been used for statistical analysis. Results: In the present study, plaque index and bleeding index was significantly more in cases than controls with a p value of 0.009 and 0.035 respectively. Evidence of periodontitis was seen in 86% of cases and 76% of controls respectively which was also statistically significant with a p value of 0.071.Moderate periodontitis was found in significant number cases and was statistically significant with a P value of <0.001. Conclusions: This suggests that there exists an association between moderate periodontitis and preterm labour and low birth weight.